2017
DOI: 10.1177/1533034617732426
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Comparison of Differentiation-Related Proteins in Hepatocellular Carcinoma Tissues by Proteomics

Abstract: Histological differentiation is a major pathological criterion indicating the risk of tumor invasion and metastasis in patients with hepatocellular carcinoma. The degree of tumor differentiation is controlled by a complex interacting network of associated proteins. The principal aim of the present study is to identify the possible differentiation-related proteins which may be used for early diagnosis and more effective therapies. We compared poorly differentiated and well-differentiated hepatocellular carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…However, the clinical importance and function of PRDX2 in HCC has not been comprehensively studied. A previous study conducted in our laboratory illustrated upregulation of PRDX2 in poorly differentiated HCC tissues by proteomic approaches and indicated the involvement of PRDX2 in HCC progression (18). Notably, in our present study, our results revealed the protein expression levels of PRDX2 in HCC tissues were relatively lower than that of their adjacent normal liver tissues, not only in all 4 matched tissue specimens, but also in the protein microarrays which were comprised of 176 paired tissue spots.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the clinical importance and function of PRDX2 in HCC has not been comprehensively studied. A previous study conducted in our laboratory illustrated upregulation of PRDX2 in poorly differentiated HCC tissues by proteomic approaches and indicated the involvement of PRDX2 in HCC progression (18). Notably, in our present study, our results revealed the protein expression levels of PRDX2 in HCC tissues were relatively lower than that of their adjacent normal liver tissues, not only in all 4 matched tissue specimens, but also in the protein microarrays which were comprised of 176 paired tissue spots.…”
Section: Discussionmentioning
confidence: 87%
“…According to our recently published research study led by Zhao et al , using 2-dimensional gel electrophoresis and matrix-assisted laser desorption ionization time-of-flight mass spectrometry, 11 different proteins were identified from 10 poorly differentiated HCC tissues and 10 well differentiated HCC tissues, among which PRDX2 was found to be upregulated in poorly differentiated HCC tissues compared to the well differentiated HCC tissues. Using bioinformatics tools, it was revealed that PRDX2 may be correlated with tumor invasion, metastasis, and poor prognosis, thus serving as a potentially useful diagnostic and therapeutic biomarker (18). However, whether the expression level of PRDX2 has clinical significance in HCC patients has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…The differentiation of HCC was associated with prognosis. The lower the degree of tumor differentiation pathologically, the higher the protein expression of invasion and metastasis, which were related to poor prognosis [ 24 ]. Another study proved that a poorly differentiated tumor hurt the recurrence and long-term survival of solitary HCC [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…7G-I). Relative to the tumor regions, ECM regions overexpressed genes involved in ECM protein production (COL1A1, COL1A2, COL6A3, COL3A1, SERPINH1), associated with HCC (THBS1, ANXA1, APP, CD44, LTBP1, HSPB1) [38, [41][42][43][44][45][46], HBV-associated HCC (HLA-E, HLA-C, THY1) [47][48][49][50][51][52][53], and vasculature formation (THBS1, ENG, CDH5, ROBO4) [54] (Fig. 7G).…”
Section: Retrieving the Vascularized Solid Tumor For Spatial Transcri...mentioning
confidence: 99%